PUBLIC SERVICE IN THE LAW ENFORCEMENT SPHERE OF UKRAINE - Груценко, Ю.І. (Modern engineering and innovative technologies, 2023)
The article states the need for consistent improvement of the system, organizational structure and competence of public service in the law enforcement sphere of Ukraine, correction of the legislative and organizational and management principles of their f